Framing Flexible Spending Accounts: A Large‐Scale Field Experiment on Communicating the Return on Medical Savings Accounts. (25th November 2019) - Leight, Jessica; Wilson, Nicholas
Abstract: Tax‐preferred health savings devices such as Flexible Spending Accounts (FSAs) and Health Savings Accounts (HSAs) offer employees potentially valuable financial instruments for directing pre‐tax earnings to eligible medical expenses. Despite their increasing popularity as an employee benefit, however, there is little causal evidence around individual demand for these accounts. This paper seeks to address this gap in the literature, reporting on a randomized controlled field experiment conducted with over 11, 000 U. S federal employees in 2017 in order to evaluate the effectiveness of targeted messages designed to increase FSA contributions. Our results suggest that the provision of basic information about FSAs delivered via an emailed employee newsletter did not affect the likelihood of contribution or the contribution level. The addition of statements about the absolute returns or relative returns offered by the accounts similarly had no significant effects, and these null effects are observed despite relatively high email open rates. We discuss explanations for the null results and the policy implications of findings from what appears to be the first health economics experiment analyzing tax incentives around health care savings.